Cost-Effectiveness of Avelumab Maintenance Therapy Plus Best Supportive Care vs. Best Supportive Care Alone for Advanced or Metastatic Urothelial Carcinoma - Xie, Qian; Zheng, Hanrui; Chen, Ye; Peng, Xingchen (Frontiers in Public Health, 2022)
Objective Avelumab (MSB0010718C) is a fully human anti-programmed cell death ligand 1(PD-L1) antibody against PD-L1 interactions and enhances immune activation against tumor cells in the meantime. Avelumab has been approved for locally advanced or metastatic urothelial cancer (mUC) after disease progression in several countries. We therefore conducted this study to evaluate the cost-effectiveness of avelumab maintenance therapy for advanced or mUC from the perspective of the United States (US) and China payer. Methods A Markov simulation model was performed based on clinical trial JAVELIN Bladder 100. Utilities and costs adopted in this analysis were derived from published literature and clinical trials. Incremental cost-effectiveness ratios (ICERs) were calculated to compare the avelumab maintenance therapy group (AVE group) and the best supportive care group (CON group). Results The ICER of the AVE group compared with the CON group were $38,369.50 and $16,150.29 per QALYs in the overall population and in the PD-L1–positive population, respectively. While the ICER of AVE group compared with CON group were $241,610.25 and $100,528.29 per QALYs in the overall population and in the PD-L1–positive population, respectively. Conclusion Avelumab maintenance therapy was a cost-effective first-line treatment compared with BSC in patients with mUC which were not progressed with platinum-based chemotherapy not only in the PD-L1–positive population but also in the overall population based on the current willingness to pay (WTP) of $150,000 in the US. It was not cost-effective both in the overall population and in the PD-L1 positive population at the WTP threshold of $30,447.09 in China.